Permasalahan Guru SD dalam Mengelola Kelas : Studi Kasus di Sekolah Dasar Negeri - Nur Aisyah Perangin-angin; Theresia Ulina Rajagukguk; Fanny Sasmitha; Najla Hana M. Tanjung; Dwi Maulidina Putri; Meylisa Cholissatun Fitri; Rahmilawati Rahmilawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to identify and examine the various challenges faced by elementary school teachers in managing classrooms. This research was conducted through a literature review using a descriptive qualitative approach by analyzing various references related to classroom management in elementary schools. The results indicate that teachers face a range of complex challenges, including limited competencies, student behavioral dynamics, inadequate learning facilities, non-contextual curricula, assessment barriers, and a lack of collaboration with parents. Most teachers still rely on monotonous lecture-based methods, have limited understanding of students’ characteristics, and often struggle with formative assessment and differentiated instruction. To address these issues, continuous professional development, revitalization of facilities, curriculum flexibility, and stronger collaboration between teachers, schools, and parents are needed to create a conducive, inclusive, and enjoyable learning environment.